A meta-analysis evaluating the intra-operative use of collagen-fibrin sealants during inguino-femoral lymphadenectomy: A new direction in reducing post-operative morbidity or another disappointment?. Issue 10 (October 2020) - Tranoulis, Anastasios; Georgiou, Dimitra; Sayasneh Mrcog, Ahmad; Inetianbor, Edmund; Papadopoulos, Andreas John; Devaja, Omer; Montalto, Stephen Attard
Abstract: Background: The intra-operative application of collagen-fibrin sealants (CFS) has emerged as a promising intervention to reduce post-operative morbidity associated with inguino-femoral lymph node dissection (IFLND). Aim: The purpose of this systematic review was to ascertain the efficacy and safety of CFS to reduce lymphatic morbidity after IFLND. Design: We systematically searched MEDLINE, SCOPUS, ClinicalTrials.gov, and Cochrane Database to identify all registered articles pertaining to the use of CFS during IFLND spanning the period Jan 1975 to April 2020. A direct-comparison meta-analysis was performed. Odds ratios (OR), standartised mean difference (SMD) and 95%| confidence intervals were calculated using the random-effect model. Results: A total of six randomised control trials (RCTs) and four observational studies were included in this study. The studies were characterised by significant clinical heterogeneity. The meta-analysis of RCTs showed that the application of CFS did neither decrease the length of drainage [SDM -0.55 (95% CI -1.34 to 0.23), p = 0.17] nor the amount of drained output [SMD 0.46 (95% CI -0.29 to 1.20), p = 0.23]. No significant different was found concerning the incidence of lymphocele(s) formation [OR 0.96 (95% CI 0.56–1.65), p = 0.88] or other wound complications. The safety profile of CFS was favourable. Conclusions: Our findings suggest that the use of CFS was not associated with difference in the incidence of lymphatic morbidity related to IFLND. In light of the limited data available and the high inter-study heterogeneity, this evidence should be interpreted with caution. More high quality RCTs are warranted to draw firmer conclusions.